Partial Unweighting in Obese Persons Enhances Tactile Transmission From the Periphery to Cortical Areas: Impact on Postural Adjustments - Fabre, Marie; Sainton, Patrick; Sutter, Chloé; Mouchnino, Laurence; Chavet, Pascale (Frontiers in Human Neuroscience, 2022)
Tactile plantar information is known to play an important role on balance maintenance and to contribute to the setting of the anticipatory postural adjustments (APAs) prior to stepping. Previous studies suggested that the somatosensory processes are not optimally functioning for obese individuals due to the increased pressure of the plantar sole resulting in balance issues. We hypothesized that decreasing the compression of the mechanoreceptors by unweighting the plantar sole would enhance tactile sensory processes leading to an increased stability and an accurate setting of the APAs in obese individuals. To test it, we recorded the somatosensory evoked potentials (SEP) by an electric stimulation of the plantar sole in natural quiet standing with eyes closed in two conditions, effective and reduced body weight in obese participants. The level of unweighting was calculated for each participant to correspond to a healthy body mass index. We showed an increase SEP amplitude in the unweighting condition compared to the effective body weight for all participants. This increase can be explained by the reduction of weight itself but also by the modified distribution of the pressure exerted onto the foot sole. Indeed, in the unweighting condition, the vertical ground reaction forces are evenly distributed over the surface of the foot. This suggests that decreasing and equalizing the pressure applied on the plantar mechanoreceptors results in an increase somatosensory transmission and sensory processes for obese persons when unweighted. Both of these observations may explain a more vigorous pressure onto the ground (APAs) prior to stepping.